Social Security Satisfaction and People’s Subjective Wellbeing in China: The Serial Mediation Effect of Social Fairness and Social Trust - Li, Na; He, Mang (Frontiers in Psychology, 2022)
Objective: To test the relationship between social security satisfaction, social fairness, social trust and people’s subjective wellbeing (SWB) in China and the serial mediation effect in this study. Methods: We utilized data (N=7978) from Chinese Social Survey (CSS) in 2017 and 2019, involving 31 provinces across the country. There were 5398 samples in 2017CSS and 2580 samples in 2019CSS selected by the research objectives. There were 4269 women and 3709 men with the average age of participants being 43 (SD = 14.41). Results: The results showed that the actual status of social security satisfaction, social fairness and trust, and SWB were greater than the theoretical status overall. Social security satisfaction (β = 0.454, p <0.001, 95% CI = [0.377, 0.423]), social fairness (β = 0.065, p <0.001, 95% CI = [-0.039, 0.124]) and social trust (β = 0.108, p <0.001, 95% CI = [0.237, 0.397]) positively influenced people’s SWB, respectively. Social fairness had a positive effect on social trust (β = 0.298, p <0.001). Social fairness and social trust partly mediated the relationship between social security satisfaction and SWB, respectively. The total effect of SWB explained is 47% in the serial mediation model. Conclusion: Satisfactory social security is likely to cause a high level of people’s SWB, social fairness and social trust. It is beneficial to form a virtuous circle in society. Allowing people to obtain satisfactory social security is conducive to social equity, promoting social trust, and improving people’s SWB.